Knowledge, Attitude, and Practice Towards Safe Antineoplastic Drug Handling: A Cross Sectional Pilot Study Among Nurses in a Teaching Hospital - Muhammad Idham Jasmiad; Aslina Mohamed Yasin; Nur Izzati Mansor; Amira Raudhah Abdullah; Noor Wahidah Mohd Nasri (Scientific Journals, 2026)
Indexed by WOS